Նորակազմութիւնները «Կնիք հաւատոյ» ժողովածուում - Գրիգորեան, Սուսաննա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В этой статье были рассмотрены неологизмы сборника «Печать веры». В рассматриваемом произведении в форме диалога даётся обобщённое описание конфессиональных, ритуальных и богословских представлений Армянской и Греческой церквей. In the present article, we have referred to the neologisms present in the collection “Seal of Faith”. A summary of the denominational, ritual, theological concepts of the Armenian and Greek Churches is given in the form of a dialogue in the work under examination. The collection “Seal of Faith” had an Anti-Chalcedonian, Anti-Nestorian orientation and aimed to defend the religious principles of the Armenian Church, refute sectarian doctrines, and strengthen the positions of the Armenian Church in the intensified religious struggle which was rather tense in the late 6th and early 7th century.
Keywords: Աստուածաբանութիւն; Լեզուաբանութիւն